Impact of an Educational Program Using Marzano's Dimensions Learning to Learn Some Basic Football Skills for Students - Haider Hussein Mohammed (Journal of Education and Sport Science, 2026)
This study aims to explore the effect of an educational program designed according to Marzano’s model of dimensions of learning on students’ acquisition of some basic skills in football, the researcher used experimental method on 60 students from faculty of Physical Education Sports Sciences at University of Maysan, divided into two groups, experimental control, each group consisting of 30 students. Educational program was implemented using Marzano's model of dimensions of learning on students in experimental group for a period of 4 weeks, with two educational units per week, as 3 educational units were allocated to each skill. Results of study showed effectiveness of educational program using Marzano's model dimensions of learning in learning some basic football skills among students in experimental group, with superiority over control group students led the researcher to recommend relying on Marzano's model dimensions of learning in learning basic skills in football, given its effectiveness in improving skill performance learning level of some basic football skills among students in experimental group.